Review of factors affecting optimal number of cavities for injection molding of polymers - Mojsovski,Kristijan; Zdraveski, Filip (Faculty of Mechanical Engineering, Ss. Cyril and Methodius University in Skopje, Republic of Macedonia, 2017)
The industry for designing and manufacturing of molds for injection molding very often faces with problem regarding optimization of number of cavities in the mold. The modern CAD and CAE can be very helpful in this process. Designer has to satisfy several parameters in regards of decreasing the costs and manufacturing time. For this purpose modern software tools are available such as SolidWorks, Master CAM and SolidWorks Plastics. This paper contains multi aspect analysis for molded plastic part manufactured to be cover element of HVAC. Factors such as production rate needs, especially mold design and costs for its manufacturing, are analyzed in this paper. Their influence on selection of optimal number of mold cavities is explained.
Keywords: injection molding; mold design; mold cavities; cost analysis